Stability of combustion waves propagating in two thermally coupled thin solid fuel layers. Issue 6 (1st November 2020) - Miroshnichenko, Taisia P.; Gubernov, Vladimir V.; Kurdyumov, Vadim N.
Abstract : In this work we investigate the linear stability of combustion waves propagating in a system of two layers of different exothermic reacting materials under conditions of thermal contact between them through the common interface using the reaction sheet approximation. The dispersion relations are found and the dependence of the stability boundary on the parameters of the model is studied. It is demonstrated that the boundaries of stable combustion wave propagation in such system can be significantly extended if the properties of the layers are properly tailored.